Perceptions of patient safety competency among graduating pharmacy, nursing, physiotherapy and medical imaging students: A cross-sectional study in Malaysia - Faizah Safina Bakrin; Haji Omar Azizi; Norihan Yusuf; Yasmin Tajuddin; Jeevasulochana Sinniah; Shasindrau Balakrishnan; Vasanthi Arjunan; Hamidah Hassan; Annamma Kunjukunju; Lokman Saim (International Pharmaceutical Federation (FIP), 2022)
Aim: The study aimed to investigate the perceptions of patient safety competency (PSC) among a sample of graduating healthcare professionals in a developing country. Methods: A cross-sectional survey on self-reported confidence in PSC was conducted among 469 graduands of pharmacy, nursing, physiotherapy and medical imaging at a private healthcare educational institution in Malaysia. Students’ confidence in six core domains of competency in the validated Health Professional Education in Patient Safety Survey (H-PEPSS) questionnaire was evaluated in the classroom and clinical settings. Results: Nursing students were the most confident in PSC followed by pharmacy, physiotherapy and medical imaging students (p <0.05) in both settings. The pharmacists’ scores in both settings were equal in all the domains except for the learning on the ‘Recognise and respond to reduce harm’ domain (p = 0.01). Conclusion: Based on H-PEPSS, the pharmacy students attained equal high levels of confidence in patient safety competency from both classroom and clinical settings.